Necrotizing gastritis: a case report - A. P., Tejas; Rajagopalan, S.; K., Rohit (International Surgery Journal, 2017)
Gangrene of the stomach is a rare and often fatal disease. It occurs when there is vascular anomalies, gastric volvulus or herniation and in infectious gastritis. A 65-year-old man was wheeled into the Emergency Department with complaints of abdominal pain for 8 hours. The pain was in the epigastric region which was severe in nature continuous and associated with nausea. There was no history of hematemesis or vomiting. The past medical history was not significant. He was HIV negative. On examination, he was in agonizing pain and tachypneic. The vital signs were temperature 98.6°F, pulse 118/minut, respiratory rate 28/minutes, BP 90/60 mmHg. Abdominal examination found diffuse tenderness with voluntary guarding and rigidity. Bowel sounds were sluggish. Rectal examination was normal. The Ryle’s tube showed hemorrhagic aspirate. Erect X-ray abdomen showed large gastric air fluid level and no evidence of pneumoperitoneum. Routine hemogram showed leukocytosis. Blood sugar level and serum urea, creatinine levels were within normal limits. After initial resuscitation with intravenous fluids and antibiotics, decision was taken to proceed for an emergency exploratory laparotomy. Gastric necrosis is a rare and fatal condition. Etiology includes thromboembolism and occlusion of major arterial supply, ingestion of corrosive agents, volvulus of the stomach, herniation of the stomach through the diaphragm, bulimia nervosa, iatrogenic gelfoam embolism, endoscopic hemostatic injections and infectious gastritis. So, the most probable cause of the gastric necrosis was infectious gastritis. It begins as phlegmonous (suppurative) gastritis (PG), and then it progresses to the lethal severe form: acute necrotizing gastritis. The few case reports of gastric gangrene are there in literature with the underlying etiological factors. Harvey et al, reported a rare case of multifocal infarction of stomach secondary to atheromatous emboli originating in a thoracic aortic aneurysm. Bradly et al, reported a case of extensive gastric necrosis in a patient with recurrent massive upper gastrointestinal hemorrhage. They found massive gastric gangrene secondary to therapeutic transcatheter embolization of the left gastric artery with fragments of gelatin sponge. Ovnat et al, reported three cases of acute obstruction of the celiac trunk. In all the three patients, the mucosa along the lesser curvature of the stomach was necrotic but the gross appearance of the stomach was only mildly ischemic. Organisms isolated from the gastric wall include hemolytic streptococci, proteus, E. coli and clostridium welchi. PG can be diagnosed by upper gastrointestinal endoscopy, CT scan, or endoscopic ultrasound. Its endoscopic findings can show purple colored gastric mucosa covered with dirty necrotic materials. Absolute diagnosis is made, most frequently at laparotomy. Gastric gangrene due to necrotizing gastritis is a rare and fatal disease. The diagnosis is usually made at laparotomy. Treatment consists of resection and feeding tube placement followed by intravenous antibiotics. Increased awareness of this rare entity may lead to more prompt diagnosis and an increased chance for patient survival.